Metakognisi dan Kaitannya dengan Self Efficacy Siswa - Asra Dewika; Fitria Rahmi; Yantri Maputra (ILIN Institute Makassar, 2021)
Self efficacy is student’s belief about their ability to accomplish task or problem. Students with high self efficacy, will be believe to resolve the problems. There were many thing that correlation with self efficacy, one of them was metacognition. Students with high metacognition will be confident to resolve problem with their ability. This research aimed to seen positive correlation of meatcognition with self efficacy students in Junior High School 1 Sijunjung. This research was a descriptive research with quantitative approach. The measuring instrument used in this study was the Metacognitive Awareness Inventory (MAI) by Schraw and Denisson (1994) and self efficacy scale by Suri (2015). Questionnaire was given to 227 subjects who were chosen by saturated sampling type. Data was analyzed using correlation product moment pearson test. The result showed that there was significant positive correlation between metacognition and self efficacy in students Junior High School 1 Sijunjung. The result of analysis correlation showed that correlation value (r) is 0,397 with p 0,000.